(3GdeYGde aj CUhd GdOjfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eMeO Hf SdjeGf Hf jhSa GdTGaYi s)
(3ChdgG (B:s
(3GeG HYO agPG eNJUQ jTJed Ydi NeSI CfhGY ef GdYdhe Gdegeg s
(3BNQgG (B:s
(3hEXgGQ BKGQ GdbhjI GdCeQ eWdb GdTQa hGdceGd adGOdGdI YdiBaVdjI GdedGFcI s
(3QJH cd Yde Ydi CHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B506 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B103 s
Keywords: (3GdeYGQa GdYGeIs